Essential oil composition, antioxidant and antibacterial activities of wild and cultivated Lavandula mairei Humbert. (February 2018) - El Hamdaoui, A.; Msanda, F.; Boubaker, H.; Leach, D.; Bombarda, I.; Vanloot, P.; El Aouad, N.; Abbad, A.; Boudyach, E.H.; Achemchem, F.; Elmoslih, A.; Ait Ben Aoumar, A.; et al.
Abstract: Lavandula mairei is an endemic and rare plant species growing in the mountains from the southeast to the southwest of Morocco. It is an aromatic and medicinal plant widely used in traditional medicine for the treatment of various diseases. To our knowledge, no data are available on the chemical composition and the biological activities of L. mairei essential oils (EOs). The aim of this study was to investigate the effect of cultivation on the chemical composition, antioxidant and antibacterial activities of EOs isolated from L. mairei . The hydrodistilled oils obtained from wild and cultivated L. mairei were analyzed by GC/MS. Twenty-three compounds were identified representing more than 98% of both EOs (wild and cultivated). Oils were characterized by high amount of carvacrol (78.29 and 76.61% for wild and cultivated EO respectively). The antioxidant and antibacterial assays revealed that the two EOs tested showed significant activities. The results highlighted that cultivation affected neither the chemical composition nor the biological activities of L. mairei . Cultivation of L . mairei may constitute an alternative to the conservation of this species. Highlights: Essential oils (EOs) of wild and cultivated Lavandula mairei were investigated. Cultivation did not affect chemical composition and biological activities of EOs. Carvacrol was the major compound in all samples. EOs showed potent antioxidant and antibacterial activities.